Optimum formulation of cathode mix for a multi-response set-up using design optimality criteria. (1st January 2014) - Das, Prasun; Mondal, Subrata
Optimal formulation of cathode mix for zinc-carbon dry cell is a challenging task to the battery manufacturers, the performance of which is characterised by a set of seven performance characteristics (responses). Standard experimental designs like Box-Behnken design, central composite designs are unable to conclude the optimal experimental setting due to the problem of infeasibility or non-orthogonality. This paper makes an attempt to determine the feasible and optimum factor setting of cathode mix formulation while optimising the multiple performance characteristics of zinc-carbon battery. First, a technically feasible and nearly orthogonal design is achieved within the design space using design optimality criteria. Then, five different multi-response optimisation techniques are applied to select the factor setting combination that simultaneously optimises all the responses. All the five methods suggest a particular combination of factors as the optimal formulation of cathode mix.